Pendampingan dan Pembuatan Akun Shopee untuk Mewujudkan Digitalisasi UMKM - Rahmawati, Alvina Eka; Ifana, Ayu Meilia; Arviana, Ekyk; Arifin, Rizal (CV. Edutechnium Indonesia, 2024)
The purpose of the mentoring and account creation activities for the Ken Ayu pecel sauce UMKM is to help develop the business, especially in terms of digital-based marketing, which is expected to create economic independence and increase business income from Ken Ayu pecel sauce. This study uses a qualitative method by conducting interviews, approaching UMKM owners, and documentation. Mentoring and account creation were carried out on August 19, 2024 at the house of Mrs. Sumarmi, Bringinan Village, Ponorogo Regency. It is hoped that with this activity, independence and expertise will be formed in carrying out digital-based marketing in order to adapt and compete with other UMKM actors. The results of this study are the success of the mentoring and account creation activities for Mrs. Sumarmi's Ken Ayu pecel sauce business in Bringinan Village in order to increase the number of sales with a wider and more efficient reach.